1995
DOI: 10.1002/bjs.1800820119
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of colour Doppler ultrasonography in detecting failure of vascular access grafts

Abstract: The predictive role of colour Doppler ultrasonography in determining the initial success and long-term patency of polytetrafluoroethylene (PTFE) vascular access grafts for haemodialysis was investigated. Two groups of patients were studied. The upper extremities of 21 patients in the control group were assessed by clinical examination only; those of 17 in a second group (Doppler group) were also assessed by ultrasonography before and after operation. Straight PTFE vascular access grafts were used between the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Maheshwa et al [7] investigated the relationship between young infants treated with erythromycin and risk of developing hypertrophic pyloric stenosis by analysis of six papers published between 1976 and 2005. Their review concludes that while more evidence is required regarding the relationship between erythromycin use and IHPS, young infants exposed to erythromycin in the first few weeks of life are at a greater risk of IHPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maheshwa et al [7] investigated the relationship between young infants treated with erythromycin and risk of developing hypertrophic pyloric stenosis by analysis of six papers published between 1976 and 2005. Their review concludes that while more evidence is required regarding the relationship between erythromycin use and IHPS, young infants exposed to erythromycin in the first few weeks of life are at a greater risk of IHPS.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified a strong relationship between exposure to erythromycin and development of IHPS [6]—with some studies identifying an eight to tenfold increase in risk of developing IHPS when erythromycin was administered in the first 2 weeks of life [7]. One theory is that erythromycin interacts with the receptors of motilin, an intestinal peptide that stimulates contraction of gut smooth muscle.…”
Section: Introductionmentioning
confidence: 99%
“…16 For grafts, values less than 500-600 ml/min are indicative of risk from impending thrombosis. [13][14][15]17 Fistulas tolerate low flows better, but flows less than 300-400 ml/min are indicative of possible problems at dialysis including recirculation and should be a cause for further ultrasound investigation.…”
Section: Ultrasound Measurement Of Access Flowmentioning
confidence: 99%
“…Several studies have shown that the Tesio catheter allows for pump speeds of 350 to 400 mL/min (1,(3)(4)(5) and delivers blood flows of 300 to 350 mL/min (6,7). Similarly, recirculation values average from 5% to 10% (4,7).…”
Section: Causes Of High Recirculation In Tesio Cathetersmentioning
confidence: 99%
“…QB is 400 mL/min and R is 0.43. Thus QA is 530 mL/min, low enough to place the access at high risk for thrombosis and indicate the likely presence of a severe stenotic lesion (2)(3)(4)(5)(6). Since QA > QB, recirculation with correct needle placement would not be expected (7).…”
Section: Implications Of High Recirculation With Line Reversalmentioning
confidence: 99%